SARS-CoV-2 secondary attack rates and risks for transmission among agricultural workers and their households in Guatemala, 2022-2023 - Carreon, Joseph Daniel; Lamb, Molly M.; Chard, Anna N.; Calvimontes, Diva M.; Iwamoto, Chelsea; Rojop, Neudy; Monzon, Jose; Plumb, Ian D.; Barrios, Edgar; del Cid-Villatoro, Julio; Arias, Kareen; Gomez, Melissa; et al. (IJID regions, 2025)
•Overall, 58% of households had ≥1 SARS-CoV-2 infection, with 63% experiencing secondary transmission.•Most (71%) index cases were adults, with over half working outside the home.•A total of 27% of transmissions occurred from asymptomatic or pre-symptomatic individuals.•Longer SARS-CoV-2 RNA shedding was associated with increased risks of secondary infections.•Agricultural workers should be prioritized for vaccines and non-pharmaceutical interventions. It is unclear whether agricultural workers working during epidemics frequently introduce respiratory infections into their homes and trigger secondary transmission. We evaluate secondary attack rates (SAR) and transmission risk in households of agricultural workers in Guatemala during the COVID-19 pandemic. Households of participants in a workplace surveillance cohort were enrolled from September 2021 to August 2023. All participants reported symptoms twice weekly and provided saliva weekly for SARS-CoV-2 reverse-transcriptase-polymerase chain reaction testing. Upon SARS-CoV-2 detection, participants submitted saliva three times per week for 4 weeks. We calculated SARs, and we estimated the risk of transmission to household contacts adjusting for demographic factors, COVID-19 vaccination status, seropositivity, and significant covariates (p ≤ 0.05) in univariable analyses. Among 83 households with 376 individuals, 48 (58%) had at least one SARS-CoV-2 infection (120 SARS-CoV-2 infections, 0.6 per 100 person-weeks), resulting in 64 secondary (SAR = 0.35, 95% confidence interval [CI] 0.28-0.43) and eight tertiary infections (tertiary attack rate = 0.07, 95% CI 0.03-0.13). The risk of secondary transmission increased by 112% among household contacts whose index cases were positive for ≥11 days (risk ratio: 2.12, 95% CI 1.29-3.49) but did not increase for those whose index case was positive for 6-10 days (risk ratio: 1.40, 95% CI 0.77-2.57) compared to those with index cases positive for ≤5 days. More than half of agricultural households became infected with SARS-CoV-2 and approximately two-thirds of these had secondary chains of transmission, especially when index cases shed SARS-CoV-2 longer.